Health Assessment of Patients with Cerebral Unruptured Aneurysms After Applying Interventional Therapy - Beata Piętkowska; Katarzyna Krystyna Snarska; Mirosława Dziekońska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. The incidence of intracranial aneurysms in the human population is determined on 15–20 at 100 thousands residents. In any case, brain aneurysm, the basis for optimal therapy and satisfactory results of treatment is early diagnosis allowing for rapid implementation specified by the patient procedure. Aim. The aim of this study is to assess the health status of patients with brain aneurysms not cracked after the application of interventional therapy. Material and Methods. The study included 20 patients diagnosed with ruptured brain is not under investigation by an intervention, hospitalized in 2011 in the Department of Neurosurgery USK in Bialystok. An analysis of medical records. Results. The study included 14 (70%) women and 6 (30%) men with unruptured brain undergoing interventional procedure. The mean age was 53.35±8.68 years (69–37 years). Aneurysm of the most 9 (45.0%) was located in the anterior communicating artery. The average hospital stay was 6.92± women 2.90 days (4–12 days) and 5.20± men 1.64 days (4–8 days) (NS). Frequently performed the test in the diagnosis of cerebral aneurysm was computed tomography, and the symptoms were headache (15, 78.7%) and syncope (3, 15.8%). Embolization was performed in (14, 70.0%) and was usually embolization aneurysm located on the internal carotid artery (5, 83.3%). No significant differences were observed with respect to the location of the aneurysm and the parameters before and after surgery. The average period of hospitalization was significantly longer in patients undergoing craniotomy (10.00±2.160 days) than embolization (5.43±1.828 days) (p=0.006). Conclusions. 1. Unruptured aneurysms of the brain were more common among women, and computed tomography was the most commonly performed diagnostic test. 2. The most common symptom of an aneurysm among women was headache, and among men fainting. 3. The most common surgical intervention was embolectomy, and hospitalization was held in elective surgery. 4. After surgery, a person with hypertension and tobacco smokers had a higher heart rate, systolic blood pressure and a shorter duration of hospitalization. In contrast, patients with headache as a symptom of an aneurysm, were hospitalized longer and had accelerated heart rate after surgery. (JNNN 2014;3(1):15–24)